Visualisasi Karakter Dan Desain Background Dua Dimensi Sebagai Aset Game Edukasi - Darma Yasa, Ngakan Putu; Novitasari, Dwi (Visualita Jurnal Online Desain Komunikasi Visual, 2025)
ABSTRACT: Currently, game applications are very popular with children and adults. Development of technology can help developers to create games with various genres, topic, storylines and design appearances. The design appearance in the game is the first asset that users will see, so skills are needed to design it to make it more attractive. The display design is the background for the game and the design of the main character or characters in the game. The appearance of the background and character design can provide an attraction for the game chosen by the user. The aim of this research is to design character, property and background designs for educational game assets. The data collection methods used are documentation, observation and literature as well as design using the design thinking method to produce two-dimensional vector-based background and character designs. Observations were made by observing several games which would be used as references in designing background and character designs. This research produces a cartoon design for an adventurous boy character and a two-dimensional background design that can be directly implemented into the game design process.